2012
DOI: 10.1364/ol.37.001499
|View full text |Cite
|
Sign up to set email alerts
|

Mode coherence measurements across a 15 THz spectral bandwidth of a passively mode-locked quantum dash laser

Abstract: The mode coherence of adjacent and non-adjacent spectral modes of a passively mode locked quantum dash (QDash) semiconductor laser are deduced through radio frequency beat-tone linewidth measurements. A wavelength conversion scheme that uses degenerate four wave mixing in a semiconductor optical amplifier is proposed which considerably extends the mode spacing beyond the limit imposed by conventional fast-photodetection and electrical spectrum analysis of around 100 GHz. Using this scheme, the mode coherence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…4 as a function of the spectral mode separation. The red circles specify the measured RF beat-tone linewidths of the QDash laser for the passive case and follow a trend in agreement with measurements performed on a similar device [7]. A quadratic trend is fitted to measured data, indicated by the solid red line, following theory outlined in [11].…”
supporting
confidence: 68%
See 3 more Smart Citations
“…4 as a function of the spectral mode separation. The red circles specify the measured RF beat-tone linewidths of the QDash laser for the passive case and follow a trend in agreement with measurements performed on a similar device [7]. A quadratic trend is fitted to measured data, indicated by the solid red line, following theory outlined in [11].…”
supporting
confidence: 68%
“…Quantum dot-based lasers can also achieve the terahertz bandwidths, but require either passive mode-locking with a saturable absorber, or active or hybrid mode-locking [8,9]. QDash lasers, on the other hand, have demonstrated passive modelocking without the use of a saturable absorber section [6,7]. In this Letter, terahertz beat-tone coherence measurements of a QDash laser when passively mode-locked and injection mode-locked using both electronic and optical master signals are demonstrated.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…This is accomplished through an analysis of the RF beat tone linewidth across the spectrum of an optical frequency comb[49]. Other experiments have attempted to quantify coherence through an optical and RF linewidth ratio as a function of mode number[50]. In both cases, the results showed that the term used to quantify coherence decreased as the spacing between observed spectral modes increased, indicating that coherence decreases with an increase in modal separation.…”
mentioning
confidence: 99%